KELAS IBU HAMIL MEMPENGARUHI TINGKAT KECEMASAN DALAM PERSIAPAN MENGHADAPI PERSALINAN PADA IBU HAMIL TRIMESTER III - Dhinny Novryanthi; Eva Martini; Eni Haryati; Sri Kurnia Dewi; Lutiyah Lutiyah; Ernawati Hamidah; Anita Novitriawati (Journal of Maternity Care and Reproductive Health, 2022)
During pregnancy, hormonal conditions tend to create instability in the body and mind so that the mother becomes more prone to panic, irritability, becomes irrational, feels anxious and worried, especially when facing childbirth. Many factors affect the mind of pregnant women so that anxiety arises during pregnancy such as myths about scary childbirth, the state of the baby in the womb and the physical changes that occur during pregnancy. Based on several studies, the prevalence of anxiety before delivery is 10.9% mild anxiety, 70.3% moderate anxiety, 18.8% severe anxiety. One of the efforts to overcome the anxiety of pregnant women facing childbirth is to form a class for pregnant women. The purpose of this study was to determine the effect of the class of pregnant women on the level of anxiety of pregnant women in the third trimester in preparation for childbirth. The design of this study used a pre-experimental population of third trimester pregnant women with total sampling technique, so the number of samples was 15 people. The research instrument used HARS to measure the level of anxiety. Data analysis was carried out univariate and bivariate using paired T-test. The results showed that the anxiety scale before the class of pregnant women with a mean of 17.87 and the anxiety scale after the class of pregnant women with a mean of 13.40 and p-value <0.05 thus there is an effect of class of pregnant women with the level of anxiety of pregnant women. Suggestions from this study to reduce anxiety and improve the quality of maternal and infant health, it is hoped that the class program for pregnant women can be carried out regularly.